Duplicate Bladder Exstrophy With Fistula: A Rare Variant of Exstrophy-Epispadias Complex - Thapa, Bijay (Journal of Nepal Paediatric Society, 2021)
Variants of exstrophy are rare anomalies seen in the spectrum of bladder exstrophy-epispadias complex. A seven day old male neonate was admitted in our department with a rare variant of duplicate bladder communicating with exstrophy bladder with fistula. Patient presented with patch of exstrophic bladder just below the low set umbilicus with a normal sized phallus and normally positioned urethral meatus. The baby was managed successfully with surgery and is under regular follow up.